ANALISIS PRAKTIK JUAL BELI MATERIAL BEKAS HARTA BENDA WAKAF DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DAN HUKUM POSITIF (Studi di Masjid Al-Muawanah Desa Kali Asin Kecamatan Tanjung Bintang Kabupaten Lampung Selatan) - Munawaroh; Liky Faizal (EKSYA : Jurnal Ekonomi Syariah, 2024)
This research is field research which uses 3 data sources, namely primary, secondary and tertiary data. This research is descriptive analysis. The collected data was analyzed qualitatively using an empirical juridical approach, namely sourced from Islamic Law and Positive Law. Based on the results of this analysis, it was found that in the practice of buying and selling used mosque waqf materials at the Al-Muawanah Mosque, Kali Asin Village, Tanjung Bintang District, South Lampung Regency, the principle of Maslahah Murlah is used. The benefit is seen from the usefulness of the waqf objects being sold and maintaining the waqf objects is lost in terms of their usefulness because maslahah is the benefit of the people. The equality of Islamic law and positive law related to the practice of buying and selling used waqf property materials that occurs in Kali Asin Village, Tanjung Bintang District, South Lampung Regency. Basically, buying and selling used waqf property material is basically not permitted, but there are provisions that allow the practice. that is, if the waqf assets no longer provide benefits and the sale will bring new benefits to the waqf assets. This cannot be separated from the aspect of the benefit of the people. The difference is that according to Islamic law it can be carried out by deliberation by the local community or with written approval from the Head of the District Religious Affairs Office based on advice from the Council as stated in the Compilation of Islamic Law in Article 225. Meanwhile, the process of changing waqf assets is according to positive law, as stated in Law Number 41 of 2004 concerning Waqf, in Article 41, changes to waqf assets can be made after obtaining written permission from the Minister with the approval of the Indonesian Waqf Board.